Pengaruh Persepsi Kemudahan Dan Kemanfaatan Elektronik Wallet Shopeepay Terhadap Kinerja Keuangan UMKM - Dieon Agatha Badarudin; Suyatmin Waskito Adi (CV. ITTC INDONESIA, 2025)
The research was conducted to determine and analyze the effect of perceived convenience and usefulness of the Shopeepay electronic wallet on the financial performance of MSMEs in Jebres District, Surakarta City. The research approach was carried out using quantitative methods using a sample of 165 respondents. The research instrument used a questionnaire and was analyzed using multiple linear regression. The results showed that later perceptions had a significant effect on financial performance, while perceived usefulness had no significant effect on the financial performance of MSMEs. The results simultaneously show that perceived convenience and perceived usefulness have a significant effect on the financial performance of MSMEs in Jebres District, Surakarta City.